Hydrophobic nanocellulose aerogel and preparation method thereof
The introduction of silicon-based hydrophobic regulators through the sol-gel method reduces the water absorption of nanocellulose aerogel, solves the problem of degradation of mechanical properties and thermal insulation effect caused by its high water absorption, and achieves excellent hydrophobicity and deformation resistance.
Patent Information
- Application Number
- CN202411870823.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The high water absorption of nanocellulose aerogels leads to a decrease in mechanical properties and a decrease in thermal insulation, limiting their application.
Hydrophobic nanocellulose aerogel is prepared by sol-gel method. By introducing independently developed silicon-based hydrophobic regulators, the void structure of the aerogel is adjusted and the water absorption of nanocellulose molecules is reduced.
The excellent hydrophobicity and deformation resistance of aerogel are achieved, the thermal insulation effect is maintained, and the application prospects in flexible products and load-bearing products are enhanced.
Smart Images

Figure BDA0005195717480000081 
Figure BDA0005195717480000091
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of aerogels, and in particular, relates to a hydrophobic nanocellulose aerogel and a preparation method thereof. Background Art
[0002] Aerogel is an ultra-light solid material with a 3D network skeleton and a highly interconnected porous structure. Traditional inorganic aerogels, such as silica aerogel, have the characteristics of large specific surface area and high porosity. In addition, they have many excellent properties, such as extremely low thermal conductivity, but they have disadvantages such as harsh preparation conditions and high brittleness. Nanocellulose aerogel in the new organic aerogel is an ultra-light solid material with good toughness, green environmental protection, and biorenewable advantages. It combines the characteristics of low density, high specific surface area and low thermal conductivity of highly porous aerogels, and has great application potential in energy storage, thermal, water purification, optics and electricity.
[0003] However, the surface of nanocellulose contains a large number of hydroxyl groups, which makes its aerogel easy to absorb water. After absorbing water, the aerogel will swell and soften, resulting in a decrease in the mechanical properties of the aerogel, and water enters the pores of the aerogel, resulting in an increase in thermal conductivity and a reduction in the thermal insulation effect of the aerogel; therefore, the high water absorption of nanocellulose aerogel greatly limits its application. In the prior art, the hydrophobic treatment of nanocellulose aerogel mainly includes two technical means, one of which is the external coating method, which applies a hydrophobic material to the surface of the aerogel product, which can effectively reduce the hydrophilicity of the aerogel material. However, the coating material has insufficient bonding performance with the pores, and falls off during long-term use, causing the performance of the product to gradually deteriorate; the second is the internal modification method, which improves the overall hydrophobicity of the gel material by introducing doping such as fluoride, but the introduction of fluoride increases the brittleness of the aerogel, and the aerogel pore structure is prone to collapse during the deformation process, which greatly limits its application in flexible products and load-bearing products. Summary of the invention
[0004] In order to solve the technical problems mentioned in the background technology, the object of the present invention is to provide a hydrophobic nanocellulose aerogel and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A method for preparing a hydrophobic nanocellulose aerogel comprises the following steps:
[0007] Step S1, co-hydrolysis: prepare a dispersion of nanocellulose and ethanol solution, add a silicon-based hydrophobic regulator and ethyl orthosilicate, adjust the pH value to 3-4.5 with formic acid, stir at 30-50 rpm for 0.8-1.3 h, and obtain a precursor solution;
[0008] Step S2, gelation: the precursor solution is heated to 40-50°C, neutralized with ammonia water under ultrasonic oscillation, and then stirred at 60-90 rpm for 1.5-2h to obtain a composite gel;
[0009] Step S3, freeze drying: the composite gel is transferred into a mold, frozen in liquid nitrogen for 5 minutes, and then transferred into a freeze dryer for freeze drying to obtain a hydrophobic nanocellulose aerogel.
[0010] Furthermore, the feed ratio of nanocellulose, silicon-based hydrophobic regulator and tetraethyl orthosilicate is 50g:4.2-6.8g:2.9-3.5g.
[0011] Furthermore, the solid content of the dispersion is 1.5-2.2 wt %, and the volume fraction of the ethanol solution is 20-30 vol %.
[0012] Furthermore, the freeze-drying parameters are: temperature of -50°C, vacuum degree of 100Pa, time of 72h; or temperature of -60°C, vacuum degree of 10Pa, time of 48h.
[0013] The silicon-based hydrophobic regulator is prepared by the following steps:
[0014] Step A1: Undecenyl alcohol and anhydrous tetrahydrofuran are mixed, dry nitrogen is introduced for protection, the temperature of the water bath is controlled at 10±2°C, stirring is applied at 60-90rpm, perfluorododecyltrichlorosilane is slowly added to react for 2.5-3h, then triethylamine is added to mix and the temperature is raised to 55-70°C, and the reaction is continued for 1.2-1.8h. After the reaction is completed, tetrahydrofuran is removed by rotary evaporation, the substrate is washed with water and dried to obtain an intermediate;
[0015] Furthermore, the feed ratio of perfluorododecyltrichlorosilane, undecenol, triethylamine and anhydrous tetrahydrofuran is 10mmol:32-35mmol:2-3mL:35-50mL, and the active chlorosilane group of perfluorododecyltrichlorosilane is fully substituted and etherified with undecenol to introduce the alkyl chain of the branched terminal olefin group.
[0016] Step A2: Mix the intermediate, γ-mercaptopropyltriethoxysilane, photoinitiator and dimethylacetamide, raise the temperature to 50-70°C, stir at 120-150 rpm, and use 150-200 W / m 2 The mixture was irradiated with ultraviolet light and reacted for 6-8 hours. After the reaction, water was added and vacuum evaporated to remove dimethylacetamide to obtain a silicon-based hydrophobic regulator.
[0017] Furthermore, the feed ratio of the intermediate, γ-mercaptopropyltriethoxysilane, photoinitiator and dimethylacetamide is 10mmol:30mmol:60-80mg:50-60mL. Under ultraviolet initiation, γ-mercaptopropyltriethoxysilane is added to the terminal olefin group of the intermediate to introduce multi-branched ethoxysilane modification.
[0018] Beneficial effects of the present invention:
[0019] The invention is based on nanocellulose and adopts a sol-gel method to prepare an aerogel material. A self-developed silicon-based hydrophobic regulator is introduced into the sol to adjust the voids of the aerogel and at the same time give the aerogel good anti-deformation stability. The silicon-based hydrophobic regulator is etherified by replacing the active chlorosilane in the molecules of undecyl alcohol and perfluorododecyltrichlorosilane, and an alkyl chain of a branched terminal olefin group is introduced to prepare an intermediate. Then, a multi-branched ethoxysilane modification is introduced by ultraviolet-induced addition of γ-mercaptopropyltriethoxysilane and the terminal olefin group of the intermediate. The silicon-based hydrophobic regulator is co-hydrolyzed with ethyl orthosilicate and then coupled with the hydroxyl group on the nanocellulose macromolecular chain to effectively reduce the water absorption of the nanocellulose molecules and the fluorine structure. The introduction greatly reduces the surface energy of the aerogel pore wall. In addition, the pores of the aerogel are tiny. Under surface tension, it is difficult for water to infiltrate the aerogel, which results in excellent hydrophobicity. Compared with the existing fluorine-containing silane doping, the fluorine structure of the silicon-based hydrophobic regulator is located at the center of the molecule, and the long-chain alkyl at the end plays a bridging support role. Firstly, it avoids the segregation and aggregation of the fluorine structure in the gel, resulting in uneven pores after drying, affecting the thermal insulation effect of the aerogel and the stability of the pore structure. Secondly, the long-chain alkyl has a toughening effect, which improves the toughness of the aerogel pore wall. Under certain deformation conditions, the pore properties can be maintained stable, and a stable thermal insulation effect can be maintained. It has broad application prospects in flexible products and load-bearing products. DETAILED DESCRIPTION
[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] Example 1, preparation of hydrophobic nanocellulose aerogel, the specific implementation process is as follows:
[0022] (1) Preparation of silicon-based hydrophobicity regulator
[0023] Step A1: Mix undecylenol and anhydrous tetrahydrofuran, introduce dry nitrogen for protection, control the temperature of the water bath at 10±2°C, apply stirring at 90rpm, slowly add perfluorododecyltrichlorosilane to react for 2.5h, then add triethylamine to mix and heat to 70°C, and continue to react for 1.2h, wherein the feed ratio of perfluorododecyltrichlorosilane, undecylenol, triethylamine and anhydrous tetrahydrofuran is 10mmol:35mmol:3mL:50mL. After the reaction, remove tetrahydrofuran by rotary evaporation, wash the substrate with water and dry it to obtain an intermediate.
[0024] Step A2: Mix the intermediate, γ-mercaptopropyltriethoxysilane, photoinitiator and dimethylacetamide, raise the temperature to 70°C, stir at 150 rpm, and use 150 W / m 2 The reaction was carried out under ultraviolet irradiation for 6 hours, wherein the feed ratio of the intermediate, γ-mercaptopropyltriethoxysilane, photoinitiator and dimethylacetamide was 10 mmol: 30 mmol: 60 mg: 60 mL, and the photoinitiator was selected from photoinitiator 1173. After the reaction was completed, water was added and the dimethylacetamide was removed by reduced pressure rotary evaporation to obtain a silicon-based hydrophobic regulator.
[0025] (2) Preparation of hydrophobic nanocellulose aerogel
[0026] Step S1, co-hydrolysis: prepare an ethanol solution (aqueous solution) with a volume fraction of 20 vol%, mix the nanocellulose and the ethanol solution, control the solid content to 1.5 wt%, ultrasonically disperse at 33 kHz for 10 min to make a dispersion, add a silicon-based hydrophobic regulator and tetraethyl orthosilicate to the dispersion, adjust the pH value to 3 with formic acid, apply 50 rpm stirring to react for 0.8 h, wherein the feed ratio of nanocellulose, silicon-based hydrophobic regulator and tetraethyl orthosilicate is 50 g: 4.2 g: 3.5 g, and the nanocellulose is selected from TL-002 type raw material, and the precursor solution is obtained.
[0027] Step S2, gelation: the precursor solution was heated to 50° C., ultrasonically oscillated at 20 kHz, neutralized by adding ammonia water, and then stirred at 90 rpm for 1.5 h to obtain a composite gel.
[0028] Step S3, freeze drying: the composite gel was transferred into a mold, frozen in liquid nitrogen for 5 minutes, and then transferred into a freeze dryer. The freeze drying parameters were set as follows: temperature of -50°C, vacuum degree of 100 Pa, and time of 72 hours, to obtain a hydrophobic nanocellulose aerogel.
[0029] Example 2, preparation of hydrophobic nanocellulose aerogel, the specific implementation process is as follows:
[0030] (1) Preparation of silicon-based hydrophobicity regulator
[0031] Step A1: Mix undecylenol and anhydrous tetrahydrofuran, introduce dry nitrogen for protection, control the temperature of the water bath at 10±2°C, apply stirring at 60rpm, slowly add perfluorododecyltrichlorosilane to react for 3h, then add triethylamine to mix and heat to 55°C, and continue to react for 1.8h, wherein the feed ratio of perfluorododecyltrichlorosilane, undecylenol, triethylamine and anhydrous tetrahydrofuran is 10mmol:32mmol:2mL:35mL. After the reaction, remove tetrahydrofuran by rotary evaporation, wash the substrate with water and dry it to obtain an intermediate.
[0032] Step A2: Mix the intermediate, γ-mercaptopropyltriethoxysilane, photoinitiator and dimethylacetamide, raise the temperature to 50°C, stir at 120 rpm, and use 200 W / m 2 The reaction was carried out under ultraviolet irradiation for 8 hours, wherein the feed ratio of the intermediate, γ-mercaptopropyltriethoxysilane, photoinitiator and dimethylacetamide was 10 mmol: 30 mmol: 80 mg: 50 mL, and the photoinitiator was selected from photoinitiator 1173. After the reaction was completed, water was added and the dimethylacetamide was removed by reduced pressure rotary evaporation to obtain a silicon-based hydrophobic regulator.
[0033] (2) Preparation of hydrophobic nanocellulose aerogel
[0034] Step S1, co-hydrolysis: prepare an ethanol solution (aqueous solution) with a volume fraction of 30 vol%, mix the nanocellulose and the ethanol solution, control the solid content to 2.2 wt%, ultrasonically disperse at 33 kHz for 10 min to make a dispersion, add a silicon-based hydrophobic regulator and tetraethyl orthosilicate to the dispersion, adjust the pH value to 4.5 with formic acid, apply 30 rpm stirring to react for 1.3 h, wherein the feed ratio of nanocellulose, silicon-based hydrophobic regulator and tetraethyl orthosilicate is 50 g: 6.8 g: 2.9 g, and the nanocellulose is selected from TL-002 type raw material, and the precursor solution is obtained.
[0035] Step S2, gelation: the precursor solution was heated to 40°C, ultrasonically oscillated at 20 kHz, neutralized by adding ammonia water, and then stirred at 60 rpm for 2 h to obtain a composite gel.
[0036] Step S3, freeze drying: the composite gel is transferred into a mold, frozen in liquid nitrogen for 5 minutes, and then transferred into a freeze dryer. The freeze drying parameters are set as follows: temperature is -60°C, vacuum degree is 10Pa, and time is 48 hours, thereby obtaining a hydrophobic nanocellulose aerogel.
[0037] Example 3, preparation of hydrophobic nanocellulose aerogel, the specific implementation process is as follows:
[0038] (1) Preparation of silicon-based hydrophobicity regulator
[0039] Step A1: Mix undecylenol and anhydrous tetrahydrofuran, introduce dry nitrogen for protection, control the temperature of the water bath at 10±2°C, apply stirring at 60rpm, slowly add perfluorododecyltrichlorosilane to react for 3h, then add triethylamine to mix and heat to 65°C, and continue to react for 1.5h, wherein the feed ratio of perfluorododecyltrichlorosilane, undecylenol, triethylamine and anhydrous tetrahydrofuran is 10mmol:33mmol:3mL:40mL. After the reaction, remove tetrahydrofuran by rotary evaporation, wash the substrate with water and dry it to obtain an intermediate.
[0040] Step A2: Mix the intermediate, γ-mercaptopropyltriethoxysilane, photoinitiator and dimethylacetamide, raise the temperature to 60°C, stir at 150 rpm, and use 180 W / m 2 The reaction was carried out under ultraviolet irradiation for 7.5 hours, wherein the feed ratio of the intermediate, γ-mercaptopropyltriethoxysilane, photoinitiator and dimethylacetamide was 10 mmol: 30 mmol: 60 mg: 60 mL, and the photoinitiator was selected from photoinitiator 1173. After the reaction was completed, water was added and the dimethylacetamide was removed by reduced pressure rotary evaporation to obtain a silicon-based hydrophobic regulator.
[0041] (2) Preparation of hydrophobic nanocellulose aerogel
[0042] Step S1, co-hydrolysis: prepare an ethanol solution (aqueous solution) with a volume fraction of 30 vol%, mix the nanocellulose and the ethanol solution, control the solid content to 1.8 wt%, ultrasonically disperse at 33 kHz for 10 min to make a dispersion, add a silicon-based hydrophobic regulator and tetraethyl orthosilicate to the dispersion, adjust the pH value to 3.5 with formic acid, apply 50 rpm stirring to react for 1.1 h, wherein the feed ratio of nanocellulose, silicon-based hydrophobic regulator and tetraethyl orthosilicate is 50 g: 5.5 g: 3.2 g, and the nanocellulose is selected from TL-002 type raw material, and the precursor solution is obtained.
[0043] Step S2, gelation: the precursor solution was heated to 40°C, ultrasonically oscillated at 20 kHz, neutralized by adding ammonia water, and then stirred at 90 rpm for 1.7 h to obtain a composite gel.
[0044] Step S3, freeze drying: the composite gel is transferred into a mold, frozen in liquid nitrogen for 5 minutes, and then transferred into a freeze dryer. The freeze drying parameters are set as follows: temperature is -60°C, vacuum degree is 10Pa, and time is 48 hours, thereby obtaining a hydrophobic nanocellulose aerogel.
[0045] Example 4, preparation of hydrophobic nanocellulose aerogel, the specific implementation process is as follows:
[0046] (1) Preparation of silicon-based hydrophobicity regulator
[0047] Step A1: Mix undecylenol and anhydrous tetrahydrofuran, introduce dry nitrogen for protection, control the temperature of the water bath at 10±2°C, apply stirring at 90rpm, slowly add perfluorododecyltrichlorosilane to react for 3h, then add triethylamine to mix and heat to 65°C, and continue to react for 1.5h, wherein the feed ratio of perfluorododecyltrichlorosilane, undecylenol, triethylamine and anhydrous tetrahydrofuran is 10mmol:35mmol:2.5mL:40mL. After the reaction, remove tetrahydrofuran by rotary evaporation, wash the substrate with water and dry it to obtain an intermediate.
[0048] Step A2: Mix the intermediate, γ-mercaptopropyltriethoxysilane, photoinitiator and dimethylacetamide, raise the temperature to 65°C, stir at 150 rpm, and use 200 W / m 2 The reaction was carried out under ultraviolet irradiation for 6.5 hours, wherein the feed ratio of the intermediate, γ-mercaptopropyltriethoxysilane, photoinitiator and dimethylacetamide was 10 mmol: 30 mmol: 80 mg: 60 mL, and the photoinitiator was selected from photoinitiator 1173. After the reaction was completed, water was added and the dimethylacetamide was removed by reduced pressure rotary evaporation to obtain a silicon-based hydrophobic regulator.
[0049] (2) Preparation of hydrophobic nanocellulose aerogel
[0050] Step S1, co-hydrolysis: prepare an ethanol solution (aqueous solution) with a volume fraction of 20 vol%, mix the nanocellulose and the ethanol solution, control the solid content to 1.5 wt%, ultrasonically disperse at 33 kHz for 10 min to make a dispersion, add a silicon-based hydrophobic regulator and tetraethyl orthosilicate to the dispersion, adjust the pH value to 4 with formic acid, apply 30 rpm stirring to react for 1.2 h, wherein the feed ratio of nanocellulose, silicon-based hydrophobic regulator and tetraethyl orthosilicate is 50 g:6.2 g:3 g, and the nanocellulose is selected from TL-002 type raw material, that is, a precursor solution is obtained.
[0051] Step S2, gelation: the precursor solution was heated to 50° C., ultrasonically oscillated at 20 kHz, neutralized by adding ammonia water, and then stirred at 90 rpm for 1.8 h to obtain a composite gel.
[0052] Step S3, freeze drying: the composite gel is transferred into a mold, frozen in liquid nitrogen for 5 minutes, and then transferred into a freeze dryer. The freeze drying parameters are set as follows: temperature is -60°C, vacuum degree is 10Pa, and time is 48 hours, thereby obtaining a hydrophobic nanocellulose aerogel.
[0053] Comparative Example 1, referring to Example 3, during the implementation process, the silicon-based hydrophobicity regulating agent was replaced with ethyl orthosilicate in equal amount, and the rest of the implementation process was exactly the same.
[0054] Comparative Example 2, in combination with the prior art, refers to Example 3, during the implementation process, the silicon-based hydrophobicity regulating agent is replaced with perfluorooctyltrimethoxysilane in equal amounts, and the rest of the implementation process is exactly the same.
[0055] Samples were taken from the aerogel material prepared as above, and the basic physical properties of the aerogel samples were tested, as shown in Table 1:
[0056] Table 1 Basic physical properties of examples and comparative examples
[0057]
[0058] From the test results in Table 1, it can be seen that the surface water contact angle of the aerogel prepared in the example is higher than 130°, showing excellent hydrophobicity, high porosity, small pore size, low thermal conductivity, and excellent thermal insulation performance.
[0059] The sample was subjected to a dynamic cyclic compression test using an electronic universal material testing machine. The compression rate was 10 mm / min, and the compression strain was set to 50%. After the cyclic compression reached the set test times, the residual compressive stress and thermal conductivity change rate of the sample were calculated, as shown in Table 2:
[0060] Table 2 Dynamic cycle compression results of embodiments and comparative examples
[0061]
[0062] It can be seen from the test results in Table 2 that after dynamic cyclic compression, the aerogel prepared in the example has a higher residual compressive stress and a lower decrease in the rate of change of thermal conductivity, indicating that the aerogel material in the example has excellent compression toughness and can maintain a stable pore structure during deformation.
[0063] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0064] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A hydrophobic nanocellulose aerogel, characterized in that: The method is prepared by sequentially co-hydrolyzing, gelling and freeze-drying nanocellulose, a silicon-based hydrophobic regulator and tetraethyl orthosilicate; The silicon-based hydrophobic regulator is prepared by the following steps: Step A1: Undecenyl alcohol and anhydrous tetrahydrofuran are mixed, dry nitrogen is introduced for protection, the temperature of the water bath is controlled at 10±2°C, stirring is applied at 60-90rpm, perfluorododecyltrichlorosilane is slowly added to react for 2.5-3h, then triethylamine is added to mix and the temperature is raised to 55-70°C, and the reaction is continued for 1.2-1.8h. After the reaction is completed, tetrahydrofuran is removed by rotary evaporation, the substrate is washed with water and dried to obtain an intermediate; Step A2: Mix the intermediate, γ-mercaptopropyltriethoxysilane, photoinitiator and dimethylacetamide, raise the temperature to 50-70°C, stir at 120-150 rpm, and use 150-200 W / m 2 The mixture was irradiated with ultraviolet light and reacted for 6-8 hours. After the reaction was completed, water was added and the dimethylacetamide was removed by vacuum rotary evaporation to obtain a silicon-based hydrophobic regulator.
2. A hydrophobic nanocellulose aerogel according to claim 1, characterized in that: The feed ratio of perfluorododecyltrichlorosilane, undecanol, triethylamine and anhydrous tetrahydrofuran is 10 mmol: 32-35 mmol: 2-3 mL: 35-50 mL.
3. A hydrophobic nanocellulose aerogel according to claim 2, characterized in that: The feed ratio of the intermediate, γ-mercaptopropyltriethoxysilane, the photoinitiator and dimethylacetamide is 10 mmol: 30 mmol: 60-80 mg: 50-60 mL.
4. The method for preparing a hydrophobic nanocellulose aerogel according to claim 3, characterized in that: The details are as follows: Step S1, co-hydrolysis: mixing nanocellulose and ethanol solution to prepare a dispersion, adding a silicon-based hydrophobic regulator and ethyl orthosilicate, acidifying with formic acid and stirring for 0.8-1.3 hours to obtain a precursor solution; Step S2, gelation: the precursor solution is heated to 40-50°C, neutralized with ammonia water under ultrasonic oscillation, and then stirred for 1.5-2h to obtain a composite gel; Step S3, freeze drying: the composite gel is transferred into a mold, frozen with liquid nitrogen to fix the shape, and then freeze dried to obtain a hydrophobic nanocellulose aerogel.
5. The method for preparing a hydrophobic nanocellulose aerogel according to claim 4, characterized in that: The feeding ratio of nanocellulose, silicon-based hydrophobic regulator and tetraethyl orthosilicate is 50g:4.2-6.8g:2.9-3.5g.
6. The method for preparing a hydrophobic nanocellulose aerogel according to claim 5, characterized in that: The solid content of the dispersion is 1.5-2.2 wt %, and the volume fraction of the ethanol solution is 20-30 vol %.
7. The method for preparing a hydrophobic nanocellulose aerogel according to claim 6, characterized in that: The pH value of the precursor solution is 3-4.
5.
8. The method for preparing a hydrophobic nanocellulose aerogel according to claim 6, characterized in that: The freeze-drying parameters are: temperature of -50°C, vacuum degree of 100Pa, time of 72h; or temperature of -60°C, vacuum degree of 10Pa, time of 48h.
Citation Information
Patent Citations
Preparation method of hydrophobic and oleophylic cellulose based aerogel
CN110128694A
Stable moisture absorption photo-thermal core-shell aerogel material and preparation method and application thereof
CN117164962A
Titanium dioxide-loaded hydrophilic oleophobic CNF aerogel and preparation method thereof
CN117960057A
Heat-insulating nano cellulose aerogel and preparation method thereof
CN117964937A
Nanofiber composite aerogel as well as preparation method and application thereof
CN118767882A